2011
DOI: 10.1128/aac.00279-11
|View full text |Cite
|
Sign up to set email alerts
|

A Small Amount of Fat Does Not Affect Piperaquine Exposure in Patients with Malaria

Abstract: Dihydroartemisinin-piperaquine is a new, highly effective, and well-tolerated combination treatment for uncomplicated falciparum malaria. The lipophilic characteristic of piperaquine suggests that administration together with fat will increase the oral bioavailability of the drug, and this has been reported for healthy volunteers. This pharmacokinetic study monitored 30 adult patients with uncomplicated falciparum malaria for 4.5 months to evaluate the effects of the concomitant intake of fat on the total pipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…This may have accounted for the lower peak concentrations and lower effects of PIP on the QT interval observed in 2013. Multiple piperaquine peak concentration increases postdosing have been observed in several studies and were possibly the result of erratic dissolution and/or absorption from gastric emptying, enterohepatic recirculation, and/or multisector intestinal absorption (7)(8)(9)(10). Other factors, including plasma protein binding of Ͼ99% (16) and moderate concentrations in red blood cells (29), limit measurement of the total level of piperaquine exposure in the body, and thus, the actual levels in myocardial tissue are unlikely to be approximated.…”
Section: Discussionmentioning
confidence: 94%
“…This may have accounted for the lower peak concentrations and lower effects of PIP on the QT interval observed in 2013. Multiple piperaquine peak concentration increases postdosing have been observed in several studies and were possibly the result of erratic dissolution and/or absorption from gastric emptying, enterohepatic recirculation, and/or multisector intestinal absorption (7)(8)(9)(10). Other factors, including plasma protein binding of Ͼ99% (16) and moderate concentrations in red blood cells (29), limit measurement of the total level of piperaquine exposure in the body, and thus, the actual levels in myocardial tissue are unlikely to be approximated.…”
Section: Discussionmentioning
confidence: 94%
“…While studies of piperaquine with modest fat intake in Vietnam (17 g) (28) and Thailand (6.4 g) (6,29) showed little or no effect on piperaquine C max or area under the concentration-time curve (AUC), other studies showed a clear increase. In a randomized crossover study of eight healthy Caucasian adults, C max and AUC of piperaquine approximately doubled with a 37-g-fat meal without altering the time to maximum concentration of drug in serum (T max ) (30).…”
Section: Discussionmentioning
confidence: 99%
“…Food intake was not controlled in the Thai study (14). Although a small amount of fat (Ͻ10 g) does not increase PQ bioavailability (47)(48)(49), greater fat intake, such as that associated with a normal meal, can as much as double relative bioavailability (50)(51)(52). It is possible that the women in the Thai study, whether pregnant or not, consumed increasing amounts of fat as they recovered from malaria, progressively increasing bioavailability as a result of the lipophilicity of PQ.…”
Section: Discussionmentioning
confidence: 99%